2016
DOI: 10.1002/14651858.cd005091.pub4
|View full text |Cite
|
Sign up to set email alerts
|

One dose per day compared to multiple doses per day of gentamicin for treatment of suspected or proven sepsis in neonates

Abstract: One dose per day compared to multiple doses per day of gentamicin for treatment of suspected or proven sepsis in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 82 publications
(13 reference statements)
0
28
0
11
Order By: Relevance
“…However, peak concentrations are rarely measured in routine neonatal practice, which is focused around gentamicin trough levels and the prevention of ototoxicity and nephrotoxicity, and we do not know the peak concentrations of participants in this study. However, the recommended gentamicin dosing regimen of 4–5 mg/kg/dose,8 which was followed by all NNUs in this study, has been shown to achieve these target peak concentrations 23…”
Section: Discussionmentioning
confidence: 73%
“…However, peak concentrations are rarely measured in routine neonatal practice, which is focused around gentamicin trough levels and the prevention of ototoxicity and nephrotoxicity, and we do not know the peak concentrations of participants in this study. However, the recommended gentamicin dosing regimen of 4–5 mg/kg/dose,8 which was followed by all NNUs in this study, has been shown to achieve these target peak concentrations 23…”
Section: Discussionmentioning
confidence: 73%
“…This PK/PD target has been reproduced in several other studies in adults [17,18] and is often utilised when deriving individualised PK dosing regimens in children. Although traditional dosing of aminoglycosides involved multiple daily administrations, optimal dosing strategies include high doses administered once daily [19,20]. Such extended-interval dosing takes advantage of the concentration-dependent bactericidal activity of the drugs and is clinically aided by the substantial PAE and leukocyte enhancement, minimising bacterial re-growth after the serum concentration has fallen below the bacterial MIC [14].…”
Section: Antibiotics With Concentration-dependent Killing With Modmentioning
confidence: 99%
“…Nephrotoxicity is linked to drug accumulation, which occurs due to binding of the medication to the brush borders of renal cells [21]. Low sustained concentrations result in more effective uptake in these tissues than when exposed to high intermittent levels [20]. Ototoxicity is due to production of free radicals that damage cochlear and vestibular hair cells [22].…”
Section: Antibiotics With Concentration-dependent Killing With Modmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is supported by observations of reduced nephrotoxicity in children, but there is only indirect (ie, more TDM observations on target) evidence in neonates 22. Extended interval dosing for aminoglycosides results in the administration of higher doses in order to achieve higher peak concentrations (C max , improved bactericidal effect) and a C max /pathogen specific minimal inhibitory concentration (MIC) ratio >8, with longer time intervals between administration resulting in lower trough concentrations (less adaptive resistance, reduced toxicity) 2 23.…”
Section: Criterion 2: the Target Range Is Known And Narrowmentioning
confidence: 98%